A Case of Eccrine Porocarcinoma: Usefulness of Immunostain for S-100 Protein in the Diagnoses of Recurrent and Metastatic Dedifferentiated Lesions - Kurisu, Yoshitaka (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2013)
Eccrine porocarcinoma is a rare malignant tumor. Immunostain for S-100 protein, in addition to epithelial membrane antigen (EMA) and carcinoembryonic antigen (CEA), is described to be useful in the diagnosis. Herein, we report a case of eccrine porocarcinoma with immunostain for S-100 protein which was useful in diagnoses of recurrent and metastatic lesions. The primary lesion in the left inguinal region was excised, but it recurred on the same site 14 months after the resection. The recurrent lesion showed epithelioid melanocytic findings. Three months later, metastasis to the lungs was found. Since these recurrent and metastatic lesions were dedifferentiated, typical histologic findings of eccrine porocarcinoma disappeared in biopsied specimens. Nevertheless, scattered immunoreactive cells for S-100 protein were maintained in these dedifferentiated lesions. S-100 protein positive cells could be an aid to diagnose, even if histologic findings of recurrent and metastatic lesions have changed by dedifferentiation.